2020
DOI: 10.1055/s-0040-1713954
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Use and Periodontal Disease: A Systematic Review

Abstract: AbstractPeriodontitis affects the teeth supporting structures, such as periodontal tissues. We aimed to evaluate the association between periodontal disease and corticosteroid use. We searched in MEDLINE, Web of Sciences, SCOPUS, LILACS, and Cochrane databases, using the descriptors “Periodontal diseases” AND (“adrenal cortex hormones” OR “adrenal cortex hormones” OR (“adrenal” AND “cortex” AND “hormones”) OR “adrenal cortex hormones” OR “corticosteroid”). We selected the summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Adults older than 73 years showed a stronger association between periodontal disease and CDK (OR 3.74, 95% CI 3.49–3.97). Our findings in this study agree with those of other authors, 1115 who identified a higher prevalence of periodontal disease in older adults. This situation represents a public health problem and places adults over 65 years of age at a 44% risk of acquiring periodontitis.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Adults older than 73 years showed a stronger association between periodontal disease and CDK (OR 3.74, 95% CI 3.49–3.97). Our findings in this study agree with those of other authors, 1115 who identified a higher prevalence of periodontal disease in older adults. This situation represents a public health problem and places adults over 65 years of age at a 44% risk of acquiring periodontitis.…”
Section: Discussionsupporting
confidence: 94%
“…Studies evaluating the association between periodontal disease and chronic use of corticosteroids in patients with CKD could confirm this association. 13 Better understanding of these associations would inform clinical management of periodontal disease in patients with CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few publications addressing the impact of corticosteroid treatment on periodontal disease, but one recent review concluded that some studies indicate an adverse effect of corticosteroids. 44 Furthermore, Fernandes et al found a positive association between the cumulative dose of corticosteroids and increase in plaque and gingival bleeding rates in patients with juvenile SLE (P = 0.01), whereas no association with the use of antimalarials or immunosuppressive agents was established. 45 Because corticosteroid treatment is part of the treatment regime for a majority of SLE patients, this could also contribute to the increased rate of periodontitis seen in the SLE-patients of our study.…”
Section: Discussionmentioning
confidence: 98%
“…A study that analyzed the effect of inhaled corticosteroids on a group of patients with chronic obstructive pulmonary disease concluded that this therapy may affect bone metabolism and cause a reduction in bone mineral density of the maxillary bones [34]. These observations were enforced by a meta-analysis that states that patients with asthma treated with corticosteroids have a higher prevalence of periodontitis compared to subjects under another therapeutic regime [35]. On the other hand, short-term use of corticosteroids might be beneficial for periodontal tissues; a study highlighted that prednisone, with or without the association of surgical therapy, was efficient in reducing inflammation periodontal parameters and salivary cortisol level in patients with chronic periodontitis [36].…”
Section: Corticosteroidsmentioning
confidence: 99%